Digital Strategies for Effective Discipleship in Urban Areas: Suggestions and Implementation Guide - Willem*, Engel Berth; Hendriks, Alvyn (Riwayat: Educational Journal of History and Humanities, 2023)
Urban society, characterized by its bustling daily activities and technological advancements, presents a unique challenge for discipleship. To effectively reach souls and nurture congregational members, a pastor must adopt innovative strategies in fulfilling the Great Commission. Urban discipleship through digital means emerges as a promising avenue to address the challenges faced by pastors amidst the digital era. This research aims to elucidate the role of digital tools for pastors in carrying out discipleship in the context of Matthew 28:19. The study employs a qualitative research approach with a descriptive methodology to implement urban discipleship in the digital era. The author suggests that pastors should harness technological advancements to reach souls and serve congregational members in the task of discipleship.Masyarakat kota yang identik dengan kesibukan dalam aktifitas kesehariaannya, serta kemajuan teknologi. Pemuridan harus tetap dilaksanakan dalam menjakau jiwa-jiwa dan anggota jemaat membuat Gembala harus mengunakan strategi baru dalam menjalankan tugas amanat agung. Pemuridan di perkotaan dengan digital ditawarkan menjadi salah satu akses yang dapat diterapkan dalam menghadapi tantangan Gembala ditenggah kemajuan dunia diera digital. Penelitian ini bertujuan untuk menjelaskan peranan digital bagi Gembala untuk melaksanakan pemuridan dalam kontek Matius 28:19. Penelitian ini mengunakan jenis penelitian kualitatif dengan pendekatan deskriptif untuk mengaplikasikan pemuridan perkotaan di era digital. Penulis menyarankan untuk Gembala dapat menerapkan kemajuan teknologi untuk menjangkau jiwa-jiwa dan anggota jemaat dalam melaksakan tugas pemuridan.